The nuclear revolution in Soviet military affairs. Transl. and ed., with introd. and commentary, by W.R. Kintner and H. Fast Scott. [With contribs of R.Y. Malinovsky (R.J. Malinovskij), N.A. Sbitov, V.V. Larionov a.o.] (University of Oklahoma Press, 1968)
With index.